Bullwhip Effect Phenomenon and Mitigation in Logistic Firm's Supply Chain: Adaptive Approach by Transobrder Agency, Canada - Riffat Faizan; Adnan Ul Haque (International Journal of Supply Chain Management, 2015)
Abstract: Purpose: This case study explores the bullwhip effect phenomenon and mitigation in supply chain process at Transborder Logistic Canada. Problem statement: Despite being one of the largest logistic chains of Canada, Transborder for two years was facing challenges and problem in shape of bullwhip effects. To add further to the firm's problem there is no owned-warehouse to manage its inventories. Theoretical Framework: The theoretical framework for present case study is based on the theory of Lee (1977) to overcome the problems in the supply chain process. Moreover, the steps of Hussain and Drake (2011) are considered to overcome the bullwhip effects, challenges of cost control, response time, risk management, and effective warehouse management. Methodology: